2020
DOI: 10.1186/s12864-020-6588-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis reveals high intra-serovar plasticity within Salmonella Napoli isolated in 2005–2017

Abstract: Background: Salmonella enterica subsp. enterica serovar Napoli (S. Napoli) is among the top serovars causing human infections in Italy, although it is relatively uncommon in other European countries; it is mainly isolated from humans and the environment, but neither the reservoir nor its route of infection are clearly defined. This serovar is characterized by high genomic diversity, and molecular evidences revealed important similarities with typhoidal serovars. Results: 179 S. Napoli genomes as well as 239 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…However, the data presented here confirm that this serovar does indeed occur in breeding birds at the top of the poultry production pyramid. Another important factor deserving particular attention is that S. Napoli has been associated with typhoidal serovars thanks to their genetic similarities, and hence, its control along the food chain is of paramount importance [10].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data presented here confirm that this serovar does indeed occur in breeding birds at the top of the poultry production pyramid. Another important factor deserving particular attention is that S. Napoli has been associated with typhoidal serovars thanks to their genetic similarities, and hence, its control along the food chain is of paramount importance [10].…”
Section: Main Textmentioning
confidence: 99%
“…Another important factor deserving particular attention is that S . Napoli has been associated with typhoidal serovars thanks to their genetic similarities, and hence, its control along the food chain is of paramount importance [ 10 ].…”
mentioning
confidence: 99%
“…According to the WHO, there over 90 million people are infected by Salmonella annually, and 150,000 people die from Salmonella infection [ 1 ]. Over 2600 Salmonella serotypes have been identified and can be referred to as typhoidal or non-typhoidal (NTS); the latter are present in different animal reservoirs and are responsible for self-limiting gastrointestinal syndromes [ 2 ]. S. Typhimurium can cause potential threat to human health through the consumption of contaminated food or water [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on epidemiological evidences collected in Italy, Leati et al (2021) suggested that other serotypes, such as Salmonella Derby and Salmonella Napoli, should be considered for control at primary production level, due to their frequent isolation in human infections. In addition, it has increasingly been reported that specific clones of different serotypes, rather than the serotype as such, are responsible for emergent spread in both humans and the food chain ( Coipan et al, 2020 ; García-Soto et al, 2020 ; Mastrorilli et al, 2020 ; EFSA and ECDC, 2021b ). Often, these clones are characterized by the acquisition of large conjugative plasmids providing resistance features and virulence-associated properties ( Franco et al, 2015 ; Alba et al, 2020 ; García-Soto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%